An alternative pathway for sweet sensation: possible mechanisms and physiological relevance - Elena von Molitor; Katja Riedel; Michael Krohn; Rüdiger Rudolf; Mathias Hafner; Tiziana Cesetti (Pflügers Archiv - European Journal of Physiology, 2020)

Anti-repulsive Guidance Molecule C (RGMc) Antibodies Increases Serum Iron in Rats and Cynomolgus Monkeys by Hepcidin Downregulation - Preethne Böser; Dietmar Seemann; Michael J. Liguori; Leimin Fan; Lili Huang; Mathias Hafner; Andreas Popp; Bernhard K. Mueller (The AAPS Journal, 2015)

Alpine climate during the Holocene: a comparison between records of glaciers, lake sediments and solar activity - Samuel U. Nussbaumer; Friedhelm Steinhilber; Mathias Trachsel; Petra Breitenmoser; Jürg Beer; Alex Blass; Martin Grosjean; Albert Hafner; Hanspeter Holzhauser; Heinz Wanner; Heinz J. Zumbühl (Journal of Quaternary Science, 2011)
The European Alps are very sensitive and vulnerable to climate change. Recent improvements in Alpine glacier length records and climate reconstructions from annually laminated sediments of Alpine Lake Silvaplana give the opportunity to investigate the relationship between these two data sets of Alpine climate. Two different time frames are considered: the last 500–1000 years as well as the last 7400 years. First, we found good agreement between the two different climate archives during the past millennium: mass accumulation rates and biogenic silica concentration are largely in phase with the glacier length changes of Mer de Glace and Unterer Grindelwaldgletscher, and with the records of glacier length of Grosser Aletschgletscher and Gornergletscher. Secondly, the records are compared with temporally highly resolved data of solar activity. The Sun has had a major impact on the Alpine climate variations in the long term, i.e. several centuries to millennia. Solar activity varies with the Hallstatt periodicity of about 2000 years. Hallstatt minima are identified around 500, 2500 and 5000 a. Around these times grand solar minima (such as the Maunder Minimum) occurred in clusters coinciding with colder Alpine climate expressed by glacier advances. During the Hallstatt maxima around 0, 2000 and 4500 a, the Alpine glaciers generally retreated, indicating a warmer climate. This is supported by archaeological findings at Schnidejoch, a transalpine pass in Switzerland that was only accessible when glaciers had retreated. On shorter timescales, however, the influence of the Sun cannot be as easily detected in Alpine climate change, indicating that in addition to solar forcing, volcanic influence and internal climate variations have played an important role. Copyright © 2011 John Wiley & Sons, Ltd.

Studies on a PMCA-like protein in the outer mantle epithelium of Anodonta cygnea: insights on calcium transcellular dynamics - Manuel Lopes-Lima; Reiner Bleher; Tassilo Forg; Mathias Hafner; Jorge Machado (Journal of Comparative Physiology B, 2008)

A new in vitro bioassay for cyst formation by renal cells from an autosomal dominant rat model of polycystic kidney disease - Roxana Pey; Juergen Bach; Gisela Schieren; Norbert Gretz; Mathias Hafner (In Vitro Cellular & Developmental Biology - Animal, 1999)